Advances and challenges in eco-benign fire-retardant polylactide. (November 2021) - Xue, Yijiao; Feng, Jiabing; Ma, Zhewen; Liu, Lina; Zhang, Yan; Dai, Jinfeng; Xu, Zhiguang; Bourbigot, Serge; Wang, Hao; Song, Pingan
Abstract: Polylactide (PLA) derived from renewable resources has drawn great interests in packaging, electronics, and automotive fields because of its biodegradability, high mechanical strength, high transparency, and ease of processing. However, inherent flammability and heavy melt dripping exceedingly impede its real-world applications in the forgoing fields. The last decade has witnessed the development of a variety of eco-benign fire retardants for PLA, but to date there has been an urgent lack of a comprehensive yet critical review on this topic. Herein, three major categories of fire retardants, organic, inorganic, and inorganic/organic FRs are reviewed, and fire retardant and mechanical properties of their PLA materials are discussed. This review highlights some representative fire retardants and their modes of actions in PLA followed by performance comparisons. Some important practical applications of fire-retardant PLA also are reviewed. Finally, key challenges with current fire-retardant PLA materials are discussed and some design principles are proposed for creating fire-retardant and mechanically robust PLA materials. Graphical abstract: Image 1 Highlights: This review reports the state-of-the-art of organic, inorganic, and inorganic/organic fire retardants. Impacts of different fire retardants on fire-retardant and mechanical properties of PLA are reviewed. Modes of action of different fire-retardant systems are discussed. Some applications for fire-retardant PLA are reviewed. Key challenges and future research opportunities for fire-retardant PLA are proposed.